2018
DOI: 10.1002/ijc.31886
|View full text |Cite
|
Sign up to set email alerts
|

Use of vitamin K antagonists and risk of prostate cancer: Meta–analysis and nationwide case–control study

Abstract: Use of vitamin K antagonists (VKAs) has been suggested to reduce the risk of prostate cancer. We conducted a nested case–control study using Danish demographic and health data registries and summarized existing evidence in a meta‐analysis. The case–control study included all Danish men aged 40–85 years with incident histologically verified prostate adenocarcinoma between 2005 and 2015 (cases). For each case, we selected 10 age–matched controls. We used conditional logistic regression to estimate odds ratios (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(104 reference statements)
0
11
0
Order By: Relevance
“…Similarly, Haaland et al ( 7 ) found a decreased PCa incidence among both warfarin users, and men with atrial fibrillation. However, not all studies have reported a decreased risk among long-term VKA users ( 5 , 6 , 8 , 9 ). Blanc-Lapierre et al ( 6 ) found a weak non-significant negative association for oral anticoagulant use and risk of PCa, while Ahern et al ( 5 ) found no evidence of an association for VKA use.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Haaland et al ( 7 ) found a decreased PCa incidence among both warfarin users, and men with atrial fibrillation. However, not all studies have reported a decreased risk among long-term VKA users ( 5 , 6 , 8 , 9 ). Blanc-Lapierre et al ( 6 ) found a weak non-significant negative association for oral anticoagulant use and risk of PCa, while Ahern et al ( 5 ) found no evidence of an association for VKA use.…”
Section: Discussionmentioning
confidence: 96%
“…A possible protective effect of VKAs on the development of PCa was first reported in 2000 ( 4 ) prompting an interest in the possible anti-PCa effect of VKAs, in particular, warfarin ( 5 12 ). However, to date evidence is conflicting, with a recent meta-analysis finding no association between VKAs and PCa risk ( 9 ). Detection bias due to reluctance to perform prostate biopsies among men on chronic oral anticoagulation therapy has been suggested as a possible explanation for decreased risk of Pca in men on warfarin ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this national population-based study, men who were treated with chronic anticoagulation for prosthetic heart valve thromboprophylaxis had lower risks of prostate cancer than men in the general population, consistent with several prior studies. 9 However, this association was greatest among men observed from 2000 to 2001, and decreased over time so that no significant difference in risk of prostate cancer was present among men who enrolled in 2008-2010 and followed to 2015. The attenuation of the protective association in the anticoagulation group corresponded with decreased use of prostate biopsies in the general population group.…”
Section: Discussionmentioning
confidence: 97%
“…Men treated with warfarin have been reported to have lower risks of prostate cancer than men not treated with warfarin in several studies . A recent meta‐analysis of eight studies indicated that the risk was ~15% lower among men treated with warfarin, although with heterogeneity among estimates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation